Classification fault events using wavelet transform and expert rules - Nattapong Praditphol (2018)
This paper presents a classification faults in electrical power systems. To improve the electric power quality, sources of disturbances must be known and controlled. Power quality disturbance waveform recognition is often troublesome because it involves a broad range of disturbance categories or classes. This is a study of fault events classification using wavelet transformation and expert rule base. Rule base is obtained for using to classify the power quality problems. The combined wavelet transformation with expert rule is able to classify all 4 types of fault events correctly.